Nutrition Interventions in Rheumatoid Arthritis: The Potential Use of Plant-Based Diets. A Review - Alwarith, Jihad; Kahleova, Hana; Rembert, Emilie; Yonas, Willy; Dort, Sara; Calcagno, Manuel; Burgess, Nora; Crosby, Lee; Barnard, Neal D. (Frontiers in Nutrition, 2019)
Rheumatoid arthritis (RA), a chronic inflammatory autoimmune disease, affects roughly 1% of the world's population. RA pathogenesis remains unclear, but genetic factors account for 50–60% of the risk while the remainder might be linked to modifiable factors, such as infectious diseases, tobacco smoking, gut bacteria, and nutrition. Dietary triggers may play an inciting role in the autoimmune process, and a compromised intestinal barrier may allow food components or microorganisms to enter the blood stream, triggering inflammation. In addition, excessive body weight may affect pharmacotherapy response and the likelihood of disease remission, as well as the risk of disease mortality. Evidence suggests that changes in diet might play an important role in RA management and remission. Several studies have shown improvements in RA symptoms with diets excluding animal products. Studies have also shown that dietary fiber found in these plant-based foods can improve gut bacteria composition and increase bacterial diversity in RA patients, thus reducing their inflammation and joint pain. Although some of the trigger foods in RA patients are individualized, a vegan diet helps improve symptoms by eliminating many of these foods. This review examines the potential role of a plant-based diet in mediating RA symptoms. Further research is needed to test the effectiveness of plant-based diets on joint pain, inflammation, and quality of life in patients with RA.